Are School Committees a Source of Empowerment? Insights from Tanzania. Issue 9 (29th July 2017) - Masue, Orest Sebastian; Askvik, Steinar
ABSTRACT: Studies on user committees often critique the claim that membership to these committees empowers people. In this article, we use survey data on empowerment school committees in Tanzania to find out whether school committee membership is a source of empowerment of people at the local levels. Our findings suggest that membership in itself has limited impact on empowerment, while access to information and gender are the major sources of empowerment. However, the role of membership to the school committee is significant insofar as it can expose members to critical information on school issues.